PENGARUH OPINI AUDIT DAN LIKUIDITAS TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG ADA DI BEI TAHUN 2018-2021 - Ginting, Raja Masmur; Malau, Harman (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
Audit opinion and liquidity are examined into variable x in this study with the aim of knowing how well the influence produced on the length of time of the audit report lag which is the y variable in this study. As a population and also samples that will be researched, it is collected first through data sampling that is carried out to focus on the same field in a certain period of time, precisely companies engaged in basic industry and chemistry in 2018 - 2021. For the test, the data obtained first will be tested for normality through multicholinearity of the data by being ascertained once again through the histogram and normal P-P Plot which is the reference. Then a multiple linear regression analysis is carried out and the next is the f test and t test and end with a coefficient of determination test to determine how much influence it produces. The results of this study show that as many as 40 financial statements that are the object of this study show that it turns out that both audit opinions and liquidity have a negative and insignificant influence on audit report lag. However, when tested simultaneously, it was found that the audit opinion and liquidity had a significant influence on the audit report lag even though it was only 17.1% according to the results on the coefficient of determination test.